Exploring the prevalence, impact and experience of cardiac cachexia in patients with advanced heart failure and their caregivers: A sequential phased study. (July 2022) - Carson, Matthew A; Reid, Joanne; Hill, Loreena; Dixon, Lana; Donnelly, Patrick; Slater, Paul; Hill, Alyson; Piper, Susan E; McDonagh, Theresa A; Fitzsimons, Donna
Background: Cardiac Cachexia is a wasting syndrome that has a significant impact on patient mortality and quality of life world-wide, although it is poorly understood in clinical practice. Aim: Identify the prevalence of cardiac cachexia in patients with advanced New York Heart Association (NYHA) functional class and explore its impact on patients and caregivers. Design: An exploratory cross-sectional study. The sequential approach had two phases, with phase 1 including 200 patients with NYHA III-IV heart failure assessed for characteristics of cardiac cachexia. Phase 2 focussed on semi-structured interviews with eight cachectic patients and five caregivers to ascertain the impact of the syndrome. Setting/participants: Two healthcare trusts within the United Kingdom. Results: Cardiac Cachexia was identified in 30 out of 200 participants, giving a prevalence rate of 15%. People with cachexia had a significantly reduced average weight and anthropometric measures ( p  < 0.05). Furthermore, individuals with cachexia experienced significantly more fatigue, had greater issues with diet and appetite, reduced physical wellbeing and overall reduced quality of life. C-reactive protein was significantly increased, whilst albumin and red blood cell count were significantly decreased in the cachectic group ( p  < 0.05). From qualitative data, four key themes were identified: (1) 'Changed relationship with food and eating', (2) 'Not me in the mirror', (3) 'Lack of understanding regarding cachexia' and (4) 'Uncertainty regarding the future'. Conclusions: Cardiac cachexia has a debilitating effect on patients and caregivers. Future work should focus on establishing a specific definition and clinical pathway to enhance patient and caregiver support.